1994
DOI: 10.1213/00000539-199408000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Scopolamine for the Reduction of Postoperative Nausea in Outpatient Ear Surgery

Abstract: We evaluated the effect of transdermal scopolamine on the incidence of postoperative nausea and vertigo after outpatient ear surgery (exploratory tympanotomy, mastoidectomy, or endolymphatic sac and oval and round window surgery) in a double-blind, placebo-controlled study. A transdermal patch containing either scopolamine (n = 19) or placebo (n = 20) was placed behind the nonsurgical ear 2 h before surgery. Anesthesia was induced with thiopental (4-6 mg/kg intravenously [i.v.]), sufentanil (0.5 microgram/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
59
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 0 publications
9
59
0
Order By: Relevance
“…Postoperative nausea and vomiting (PONV) are distressing and frequent adverse events after general anaesthesia and surgery [1] and patients who undergo middle ear surgery may be especially at risk of experiencing these problems. In the absence of any anti-emetic treatment, the incidence of PONV following middle ear surgery ranges from 62% to 80% [2,3]. We have recently demonstrated that granisetron, a selective 5-hydroxytryptamine type 3 (5-HT3) receptor antagonist, reduces the incidence of PONV after middle ear surgery [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative nausea and vomiting (PONV) are distressing and frequent adverse events after general anaesthesia and surgery [1] and patients who undergo middle ear surgery may be especially at risk of experiencing these problems. In the absence of any anti-emetic treatment, the incidence of PONV following middle ear surgery ranges from 62% to 80% [2,3]. We have recently demonstrated that granisetron, a selective 5-hydroxytryptamine type 3 (5-HT3) receptor antagonist, reduces the incidence of PONV after middle ear surgery [4].…”
mentioning
confidence: 99%
“…In the absence of any anti-emetic treatment, the incidence of PONV following middle ear surgery ranges from 62% to 80% [2,3]. We have recently demonstrated that granisetron, a selective 5-hydroxytryptamine type 3 (5-HT3) receptor antagonist, reduces the incidence of PONV after middle ear surgery [4].…”
mentioning
confidence: 99%
“…Honkavaara et al [1] and Reinhart et al [2] observed the incidence of PONV was as high as 60-80% in patients undergoing general anaesthesia for middle ear surgery. This incidence may justify the use of prophylactic antiemetics for the prevention of PONV after middle ear surgery [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative nausea and vomiting (PONV) occur frequently after middle ear surgery, with an incidence as high as 80% when no prophylactic antiemetic is given [1,2]. This can cause significant patient discomfort, electrolyte disturbances, and may lead to delay in resumption of normal activities after elective surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This shows very high susceptibility of these patients for postoperative vomiting. The cause of vomiting after middle ear surgery is not known but many factors play their role including patients demography, history of motion sickness, anesthetic used [11,12]. Thus probably more effective antiemetic will be required for these surgeries such as combination of ondansetron and dexamethasone (Fujii et al 1998) [6].…”
Section: Discussionmentioning
confidence: 99%